Pertanggungjawaban Hukum Pemerintah Desa dalam Pelayanan Publik kepada Masyarakat - Tarman Tarman; Mansyur Mansyur; Wawan Wawan; Muhamad Jamalih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Public service is one of the main functions of village government as the leading governmental organization that directly relates to the community. This study examines